USE OF BIOFUELS BY PUBLIC ROAD TRANSPORT AS ONE OF THE INSTRUMENTS TO STIMULATE THE DEMAND FOR BIOFUEL IN UKRAINE - Trypolska, G. (Institute of Renewable Energy National Academy of Sciences of Ukraine, 2019)
The paper focuses on the state of art of biofuels market development in Ukraine. The reasons for biofuels production in Ukraine are the need to load existing sugar refineries, create new and maintain the existing jobs, improve the environmental situation in cities and partially replace imports of fossil fuels. The purpose of the article is to calculate whether the use of motor biofuels in the public transport system (in particular, by buses) will be sufficient to meet the obligations provided for by the National Renewable Energy Action Plan for the period up to 2020. This topic is particularly timely, given that the predominant share of petrol and diesel is imported by Ukraine, and almost all of the country's biodiesel feedstock (first of all rape seed) grown in the country is exported. It is determined that by 2019 biofuels in Ukraine are practically not produced. There is foreign experience of use of high particles of a biological component in fuel up to the complete replacement of fossil fuels (eg. fuel В100), which is produced for specific target groups such as buses, trucks, and the like. Based on available statistical data and assumptions, the use of bioethanol by buses for the complete replacement of biofuels, as determined by the National Renewable Energy Action Plan, is proved unrealistic, as high share of passenger buses is privately owned, as well as because buses are technically not adapted to use a high proportion of biofuels. Accordingly, other tools to stimulate the use of bioethanol are needed, such as blending mandate requirement. The use of biodiesel by buses is calculated to reach only 2% of the required calculated amount of diesel fuel. Given the availability of biodiesel in the market, such a volume of diesel fuel consumption in the system of communal passenger transport is quite realistic. Ref. 17, tabl.2, fig. 2.